Informatization of intra-school work on recording meta-subject results of mastering general education programs - Gureev, Sergei M. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ Informatizat͡s︡ii͡a︡ obrazovanii͡a, 2025)
Problem Statement. Federal state educational standards of general education require the assessment of meta-subject results of mastering educational programs. Each organization implementing accredited general education programs must comply with this requirement. This activity must be reflected in the information products of the internal system of assessing the quality of education and the information and educational environment of the institution. Due to the information openness of educational organizations, information about the educational results of students in a generalized form must be available on the official websites of the organizations. Studying the information on official websites makes it possible to assess the level of informatization of in-school work on assessing meta-subject results. Thus, a relevant objective is to analyze the current situation with the organization of activities to record the meta-subject results of mastering general educational programs. Methodology. An analysis of self-assessment reports for the presence of meta-subject results was conducted on a sample of 100 schools. The electronic gradebook used in these schools were examined for the presence of technical capabilities for recording meta-subject results, using methods of statistical analysis, text analysis, data visualization, etc. Results. It was found that more than 40% of educational organizations do not mention meta-subject results in reports, and another quarter limit themselves to formal phrases. Only 21% of schools provide qualitative or quantitative data on this category of results. None of the electronic gradebooks studied contain a full-fledged module for recording meta-subject results, which significantly limits the possibilities for their analysis and visualization. Conclusion. The identified low level of computerization of the recording of meta-subject results demonstrates the need to improve digital tools that provides individual record ing of educational results.